PENINGKATAN THINKING SKILLS SEBAGAI UPAYA KESIAPAN GURU BERKUALITAS MELALUI PRAKTIK PENGALAMAN LAPANGAN - Umi Kulsum (Jurnal Guru Kita PGSD, 2021)
Abstract: Improvement of Thinking Skills As An Effort Quality Teacher Readiness Through The Field Experience Practice. The purpose of this study is to describe the improvement of thinking skills as an effort to improve adequate competence so that they become quality teachers through the practice of field experience .The scope of this research is as a form of implementation of Teacher Profesional Education (TPE) in the position of 2019 majoring in Fashion Management organized by the State University of Malang. The place for implementing Field Experience Practices (FEP) in partner schools is Vocational High School 5 Malang. Data collection uses quantitative and qualitative data mixing strategies, with sequential explanatory methods. There is a process assessment and product assessment. The results obtained show good results. An increase in the average value of the Learning Implementation Plan by 7.06 acquisition from 79.07 to 86.13. The implementation of learning also increased by an average of 7.07 gains from 78.97 to 86.04. Assessment of non-teaching activities, involvement in routine activities in schools 86.00. Personality and social competency assessment obtained an average value of  92.33. In conclusion, the FEP influences the improvement of thinking skills in the readiness of teachers who have adequate and professional characteristics and competencies for the TFE participants in positions. Keywords : thinking skills, the readiness of qualified teachers, practice field experience                   Abstrak: Peningkatan Thinking Skills Sebagai Upaya Kesiapan Guru Berkualitas Melalui Praktik Pengalaman Lapangan. Tujuan penelitian ini untuk mendeskripsikan peningkatan thinking skills sebagai upaya meningkatkan kompetensi yang memadai sehingga mereka menjadi guru berkualitas melalui praktik pengalaman lapangan (PPL). Ruang lingkup penelitian ini sebagai bentuk implementasi Pendidikan Profesi Guru (PPG) dalam jabatan 2019 jurusan Tata Busana yang diselenggarakan Universitas Negeri Malang. Tempat pelaksanaan PPL di sekolah mitra yaitu SMKN 5 Malang. Pengumpulan data menggunakan strategi mixing data kuantitatif dan kualitatif, dengan metode eksplanatoris sekuensial. Ada penilaian proses dan penilaian produk. Hasil yang diperoleh menunjukkan hasil yang baik. Terjadi peningkatan rata-rata nilai RPP sebesar 7.06 perolehan dari 79,07 menjadi 86,13. Pelaksanaan pembelajaran juga meningkat rata-rata 7,07 perolehan dari 78,97 menjadi 86,04. Penilaian kegiatan non-mengajar, keterlibatan dalam kegiatan rutin di sekolah  86,00. Penilaian kepribadian dan kompetensi sosial diperoleh nilai rata-rata 92,33. Kesimpulan, PPL berpengaruh terhadap peningkatan thinking skills dalam kesiapan guru yang memiliki karakteristik dan kompetensi yang memadai secara profesional dan berkualitas bagi para peserta PPG Daljab. Kata kunci: thinking skills, kesiapan guru yang berkualitas, praktik pengalaman lapangan